First total synthesis of a novel amide alkaloid derived from Aconitum taipeicum and its anticancer activity. Issue 2 (17th January 2018) - Zhang, Xinxin; Li, Dandan; Xue, Xuanji; Zhang, Yan; Zhang, Jie; Huang, Chen; Guo, Zengjun; Tadesse, Nigatu
Abstract: A concise total synthesis of a naturally occurring 3-isopropyl-tetrahydropyrrolo[1, 2-a]pyrimidine-2, 4(1H, 3H)-dione (ITPD) isolated from Aconitum taipeicum with a three-step approach was depicted in this study for the first time. Two key intermediates, diethyl isopropylmalonate (2 ) and pyrrolidin-2-amine (3 ), being synthsesised separately from initial diethyl malonate (4 ) and 3, 4-dihydro-2H-pyrrol-5-amine (5 ), were utilised to obtain the compound entitled ITPD. ITPD showed a promising anticancer activity in vitro on SMMC-7721 cell lines. Flow cytometry and cell cycle analysis revealed that ITPD could induce apoptosis and cell cycle arrest in S phase. The occurrence of apoptosis possibly attributed to the mechanism that ITPD could mediate the mitochondrial pathway through activating caspase-3/9 and increasing the ratio of Bax/Bcl-2 to finally trigger cell apoptosis and DNA damage. Collectively, the possibility to produce sufficient quantity of synthetic ITPD provided the base for further bio-evaluation in vivo and in vitro . The bioactive assay suggested that it may be a potential candidate for further chemical optimisation and use in cancer therapy. Abstract :